2015
DOI: 10.1002/2015wr016947
|View full text |Cite
|
Sign up to set email alerts
|

Capillarity and wetting of carbon dioxide and brine during drainage in Berea sandstone at reservoir conditions

Abstract: The wettability of CO 2 -brine-rock systems will have a major impact on the management of carbon sequestration in subsurface geological formations. Recent contact angle measurement studies have reported sensitivity in wetting behavior of this system to pressure, temperature, and brine salinity. We report observations of the impact of reservoir conditions on the capillary pressure characteristic curve and relative permeability of a single Berea sandstone during drainage-CO 2 displacing brine-through effects on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 73 publications
(156 reference statements)
5
43
0
Order By: Relevance
“…On the other hand, Pentland et al (), Pini et al (), and Pini and Benson () performed core‐flooding experiments on Berea sandstone rock cores that all showed predictable water‐wet capillary scaling behavior indicating no changes of the water‐wet conditions in the presence of scCO 2 . Recent work by Al‐Menhali et al () investigated the impact of pressure, temperature, and brine salinity on the capillarity and wetting properties of CO 2 and brine in Berea sandstone, and the authors observed that the wettability of the CO 2 ‐brine‐sandstone system was insensitive to reservoir conditions and that the system was strongly water wet and could be characterized by analog fluids. Evidence against wettability alteration is also shown by X‐ray fluorescence measurements of stable thick brine films on smooth and rough silica surfaces under reservoir scCO 2 conditions (Y. Kim et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Pentland et al (), Pini et al (), and Pini and Benson () performed core‐flooding experiments on Berea sandstone rock cores that all showed predictable water‐wet capillary scaling behavior indicating no changes of the water‐wet conditions in the presence of scCO 2 . Recent work by Al‐Menhali et al () investigated the impact of pressure, temperature, and brine salinity on the capillarity and wetting properties of CO 2 and brine in Berea sandstone, and the authors observed that the wettability of the CO 2 ‐brine‐sandstone system was insensitive to reservoir conditions and that the system was strongly water wet and could be characterized by analog fluids. Evidence against wettability alteration is also shown by X‐ray fluorescence measurements of stable thick brine films on smooth and rough silica surfaces under reservoir scCO 2 conditions (Y. Kim et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of the trapping mechanisms depends on various geological and hydraulic parameters, including geological reservoir heterogeneities, caprock properties, CO 2 ‐rock wettability, reservoir temperature, wettability heterogeneity, and brine salinity . Moreover, although many geological parameters cannot be changed for a particular site, it has been shown that intelligent selection of CO 2 injection technology (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…These mechanisms include structural trapping (caprock barrier), 8,9 capillary trapping, [10][11][12][13][14][15][16] solubility trapping [17][18][19] and mineral trapping. [20][21][22][23][24][25] The effectiveness of the trapping mechanisms depends on various geological and hydraulic parameters, including geological reservoir heterogeneities, [26][27][28][29][30][31][32][33][34][35] caprock properties, 8,36 CO 2 -rock wettability, 26,[37][38][39][40][41][42][43] reservoir temperature, 44 wettability heterogeneity, 44 and brine salinity. 45,46 Moreover, although many geological parameters cannot be changed for a particular site, it has been shown that intelligent selection of CO 2 injection technology (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Wettability is the tendency of a fluid to preferentially wet a solid surface in the presence of other fluid(s) (Anderson, 1986a;Donaldson & Alam, 2008a). Understanding the wettability of natural rocks has significant applications in petroleum reservoir engineering (Bultreys, Van Hoorebeke, et al, 2016;Kallel et al, 2016;Suicmez et al, 2008), cleanup of underground reservoirs contaminated by nonaqueous phase liquids (Al-Futaisi & Patzek, 2004;Essaid et al, 2015), and CO 2 sequestration in subsurface geological formations (Al-Menhali et al, 2015;Chaudhary et al, 2013Chaudhary et al, , 2015Iglauer et al, 2015). Wettability impacts (a) fluids distribution at the pore scale, (b) irreducible water saturation, (c) efficiency of an immiscible displacement such as water flooding in hydrocarbon reservoirs, (d) rock-fluid properties such as capillary pressure and relative permeability, and (e) electrical properties of porous media (Peters, 2012).…”
Section: Introductionmentioning
confidence: 99%